Transformaci6n martensítica en β-Cu-Zn. - Ahlers, Manfred Hermann; Pascual, M.; Arneodo,W.; Cácerea, H.; Rapacioli, R. (Asociación Físca Argentina, 1973)
Fil: Ahlers, M. Comisión Nacional de Energía Atómica; Argentina